Free-breathing high-pitch 80 kVp dual-source computed tomography of the pediatric chest: Image quality, presence of motion artifacts and radiation dose. Issue 89 (April 2017) - Bodelle, Boris; Fischbach, Constanze; Booz, Christian; Yel, Ibrahim; Frellesen, Claudia; Beeres, Martin; Vogl, Thomas J.; Scholtz, Jan-Erik
Abstract: Objectives: To investigate image quality, presence of motion artifacts and effects on radiation dose of 80 kVp high-pitch dual-source CT (DSCT) in combination with an advanced modeled iterative reconstruction algorithm (ADMIRE) of the pediatric chest compared to single-source CT (SSCT). Materials and methods: The study was approved by the institutional review board. Eighty-seven consecutive pediatric patients (mean age 9.1 ± 4.9 years) received either free-breathing high-pitch (pitch 3.2) chest 192-slice DSCT (group 1, n = 31) or standard-pitch (pitch 1.2) 128-slice SSCT (group 2, n = 56) with breathing-instructions by random assignment. Tube settings were similar in both groups with 80 kVp and 74 ref. mAs. Images were reconstructed using FBP for both groups. Additionally, ADMIRE was used in group 1. Effective thorax diameter, image noise, and signal-to-noise ratio (SNR) of the pectoralis major muscle and the thoracic aorta were calculated. Motion artifacts were measured as doubling boarders of the diaphragm and the heart. Images were rated by two blinded readers for overall image quality and presence of motion artifacts on 5-point-scales. Size specific dose estimates (SSDE, mGy) and effective dose (ED, mSv) were calculated. Results: Age and effective thorax diameter showed no statistically significant differences in both groups. Image noise and SNR were comparable ( p >  0.64) for SSCT and DSCT with ADMIRE, while DSCT with FBP showed inferior results ( p <  0.01). Motion artifacts were reduced significantly (p = 0.001) with DSCT. DSCT with ADMIRE showed the highest overall IQ ( p  < 0.0001). Radiation dose was lower for DSCT compared to SSCT (median SSDE: 0.82 mGy vs. 0.92 mGy, p  < 0.02; median ED: 0.4 mSv vs. 0.48 mSv, p  = 0.02). Conclusions: High-pitch 80 kVp chest DSCT in combination with ADMIRE reduces motion artifacts and increases image quality while lowering radiation exposure in free-breathing pediatric patients without sedation.